2017
DOI: 10.1111/aos.13371
|View full text |Cite
|
Sign up to set email alerts
|

Serum from plasma rich in growth factors regenerates rabbit corneas by promoting cell proliferation, migration, differentiation, adhesion and limbal stemness

Abstract: s-PRGF promotes proliferation and migration and influences limbal stemness, adhesion and fibrosis during corneal healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…It has been widely used in oral implantology and traumatology in order to enhance wound healing [29][30][31]. With this same purpose, it has been used in ophthalmology to treat ocular surface diseases such as persistent epithelium defects (PED) and other pathologies [32][33][34][35][36]. It contributes to the acceleration of the healing process by increasing the proliferation and migration rate of cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in oral implantology and traumatology in order to enhance wound healing [29][30][31]. With this same purpose, it has been used in ophthalmology to treat ocular surface diseases such as persistent epithelium defects (PED) and other pathologies [32][33][34][35][36]. It contributes to the acceleration of the healing process by increasing the proliferation and migration rate of cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been contradicting results in past research, some of which revealed PRGF as the most potent blood derived product [12,33]. Differences in study designs regarding use of control groups may be a contributing factor to the significant differences in results [13]. Furthermore, variable production processes for PRGF and PRP may significantly influence the outcome of in vitro studies and clinical trials [19].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies on the beneficial properties of PRP in equine orthopaedic disorders and wound healing exist [5][6][7][8]. Recently, PRP and plasma rich in growth factors (PRGF) have been introduced in human ophthalmology, with promising results [9][10][11][12][13]. PRP has proven particularly beneficial in the treatment of nonhealing corneal ulcers, otherwise resistant to medical therapy [10].…”
Section: Introductionmentioning
confidence: 99%
“…Limbal stem cell deficiency may cause recurrent corneal epithelial erosions, inflammatory reactions and ingrowth of fibro-vascular tissue onto the corneal surface. Removal of the diseased tissue and transplantation of ex vivo engineered epithelium may restore the integrity of the corneal surface (Pellegrini et al 1997;Nakamura et al 2004;Sangwan et al 2011;Pathak et al 2013;Romero et al 2014;Zakaria et al 2014;Ljubimov & Saghizadeh 2015;Szab o et al 2015;Etxebarria et al 2017;Liu et al 2017). Removal of the diseased tissue and transplantation of ex vivo engineered epithelium may restore the integrity of the corneal surface (Pellegrini et al 1997;Nakamura et al 2004;Sangwan et al 2011;Pathak et al 2013;Romero et al 2014;Zakaria et al 2014;Ljubimov & Saghizadeh 2015;Szab o et al 2015;Etxebarria et al 2017;Liu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical symptoms include ocular pain and loss of vision (Tseng 1996;Dua et al 2000). Removal of the diseased tissue and transplantation of ex vivo engineered epithelium may restore the integrity of the corneal surface (Pellegrini et al 1997;Nakamura et al 2004;Sangwan et al 2011;Pathak et al 2013;Romero et al 2014;Zakaria et al 2014;Ljubimov & Saghizadeh 2015;Szab o et al 2015;Etxebarria et al 2017;Liu et al 2017). For such engineering, a sample containing limbal epithelium is removed from the donor eye, and cultures may be initiated by the suspension culture technique or by the explant culture technique.…”
Section: Introductionmentioning
confidence: 99%